2017
DOI: 10.2298/abs170327016m
|View full text |Cite
|
Sign up to set email alerts
|

All-trans retinoic acid influences viability, migration and adhesion of U251 glioblastoma cells

Abstract: Glioblastoma (GBM) is one of the most aggressive and deadly forms of cancer. Literature data reveals that all-trans retinoic acid (ATRA) has anticancer effects on different types of tumor cells. However, data about the effects of ATRA on glioblastoma cells are contradictory. In this study, we examined whether ATRA treatment affects features of human glioblastoma U251 cells. To that end, the cells were treated with different concentrations of ATRA. Results obtained by MTT and the crystal viole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Additionally, the proliferation of GL-15 GBM cells was inhibited by two structurally related RARγ agonists, CD-437 and CD-2325 [ 402 ]. In vitro experiments using GBM cell lines demonstrated that ATRA might induce morphological changes, differentiation, apoptosis, change in the mode of cell migration and reduction in growth, proliferation, invasiveness and adhesion of these cells [ 403 , 404 , 405 , 406 ]. Additionally, ATRA increased the asymmetric cell division of GSCs isolated from the U87 GBM cell line [ 407 ], induced differentiation and decreased proliferation and invasiveness of U87 cancer stem-like cells [ 408 ], induced morphology changes, growth arrest and differentiation of GBM stem-like cells [ 409 ] and induced differentiation and apoptosis and reduced proliferation and self-renewal of neurospheres of GBM therapy-resistant cancer stem cells [ 410 ].…”
Section: Targeting Retinoic Acid Signaling Pathway In Gbmmentioning
confidence: 99%
“…Additionally, the proliferation of GL-15 GBM cells was inhibited by two structurally related RARγ agonists, CD-437 and CD-2325 [ 402 ]. In vitro experiments using GBM cell lines demonstrated that ATRA might induce morphological changes, differentiation, apoptosis, change in the mode of cell migration and reduction in growth, proliferation, invasiveness and adhesion of these cells [ 403 , 404 , 405 , 406 ]. Additionally, ATRA increased the asymmetric cell division of GSCs isolated from the U87 GBM cell line [ 407 ], induced differentiation and decreased proliferation and invasiveness of U87 cancer stem-like cells [ 408 ], induced morphology changes, growth arrest and differentiation of GBM stem-like cells [ 409 ] and induced differentiation and apoptosis and reduced proliferation and self-renewal of neurospheres of GBM therapy-resistant cancer stem cells [ 410 ].…”
Section: Targeting Retinoic Acid Signaling Pathway In Gbmmentioning
confidence: 99%